The multiple realization of human color vision revisited - Aizawa, Ken (Frontiers in Psychology, 2022)
Over the last twenty-five years, there has been a concerted effort to settle questions about multiple realization by bringing detailed scientific evidence to bear. Ken Aizawa and Carl Gillett have pursued this scientific approach to multiple realization with a precise theory and applications. This paper reviews the application of the Dimensioned approach to human color vision, addressing objections that have appeared in the literature.